Papers - Constitution and Thermal Treatment - Carbides in Low-chromium Steel (T. P. 1436) - Walter Crafts; C. M. Offenhauer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1942)
IN the course of study of the heat-treatment of low-alloy steels, the behavior of alloy carbides at subcritical temperatures was found to vary from that indicated by published investigations. In order to establish the ranges of formation of carbides in low-chromium steels, a series of steels containing up to 0.60 per cent carbon and 7.5 per cent chromium has been investigated with respect to the type of carbide formed after quenching and tempering at sub-critical temperatures. The types of carbide formed as products of austenite transformation to pearlitic and pseudomartensitic structures have also been determined. There have been numerous investigations of the carbides in chromium steels and diagrams of the iron-chromium-carbon system.' Westgren, Phragrnén and Ne-gresco2 identified the following carbides in chromium steels: Cementitc............ Fe3C (containing up to about 15 per cent Cr) Trigonal carbide...... Cr7C3 (containing up to about 55 per cent Fe) Cubic carbide........ Cr4C (or Cr23C6) (con- . taining up to about 25 per cent Fe) Orthorhombic carbide , cr3c2 (containing only a few per cent Fe) The most complete information on the iron-chromium-carbon system was supplied by Tofaute, Sponheuer and Bennek3 and by Tofaute, Küttner and Büttinghaus,4 By means of dilatometric and microscopic stzdies, sections of the diagram were established. This diagram showed the presence of the special carbide CI7C3 in steels containing about 2.5 per cent to 12 per cent chromium in low-carbon steels and from about 5 to 20 per cent chromium in I per cent carbon alloys from A1 to room temperature. The present investigation has shown that a carbide inversion from Fe3C to Cr7C3 occurs in chromium steels containing more than about I per cent chromium after hardening and tempering at subcritical temperatures above about 500°C. The type of carbide observed to be more stable in quenched and tempered specimens was also found to be produced by direct austenite transformation in corresponding ranges of temperature and composition. Experimental Procedure The steels used in these experiments were made in magnesia-lined crucibles in high-frequency furnaces and were poured into 2-in. ingots. The ingots were forged into I-in. round bars, and all heat-treatments were conducted on specimens of this section size. Sections of the bar stock 8 in. long were hardened in air, oil or water, depending on the composition, after heating to a temperature sufficiently high to dissolve the carbides. The low-carbon and low-chromium steels were not entirely martensitic after quenching, and contained some ferrite and pseudomartensite. No pearlite was observed in the microstructures after quenching. The quenched bars were cut into